Use of polymerase chain reaction for early identification of Mycobacterium tuberculosis in positive cultures. Issue 7 (July 1992) - Cormican, M G; Barry, T; Gannon, F; Flynn, J
Abstract : AIMS: To develop a readily applicable polymerase chain reaction (PCR) based technique which would permit the identification of Mycobacterium tuberculosis complex isolates from Bactec phials at an earlier stage than currently available methods. METHODS: Mycobacterial cells cultured in Bactec 12B medium were harvested by centrifugation. The cells were lysed by heating in distilled water. Oligonucleotide primers based on the sequence of the gene coding for the immunogenic protein MPB64 were then used to amplify a 240 base pair fragment of DNA directly from the crude cell lysate. The PCR product was visualised under ultraviolet light following electrophoresis of an aliquot in an agarose gel containing ethidium bromide. The sensitivity of the PCR was adjusted so that about 600 cfu of M tuberculosis gave a positive result. The lowest growth index at which this method of identification might be applied to Bactec phials was determined and a number of routine cultures giving a positive growth index examined. RESULTS: M tuberculosis was positively identified at the lowest growth index, as determined by the Bactec system. Of 45 routine cultures examined, with growth indexes ranging from 6 to 999, the 15 confirmed by conventional means to contain M tuberculosis were correctly identified from 1 ml of culture medium. CONCLUSIONS: The method described can be used to identify M tuberculosis isolates cultured in the Bactec system at the earliest detectable rise in growth index. It may therefore allow cultured mycobacteria to be identified at an earlier stage than conventional methods or the commercially available DNA probes adapted for use with the Bactec system.